Development of climate change scenarios for small areas in Vietnam by using the MAGICC/SCENGEN software in combination with statistic correction - Cuong, Hoang Duc (VNU Journal of Science: Earth and Environmental Sciences; Vol 26 No 4, 2010)
Abstract. Climate change has beea happening in scales of the global, regional as well as Ù 1 Vietnam because o f human activities which impulse greenhouse gas increasing in the atmosphere. To cope eíĩectively with climate change, the understanding o f future climate based on climate change scenarios, particularly scenarios for small areas, is essential. This paper concerns on ứie application o f M AGICC/SCENGEN 5.3 software in combination with statistic correction to develop climate change scenarios for small areas in Vietnam. Results showed that the temperature is increased, while rainfall is changed heterogeneity and seasonally in the regions in Vietnam. Keywords: climate change scenario, MAGICC/SCENGEN.